2023
DOI: 10.1227/neu.0000000000002430
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Extent of Ablation on Survival of Patients With Newly Diagnosed Glioblastoma Treated With Laser Interstitial Thermal Therapy: A Large Single-Institutional Cohort

Abstract: BACKGROUND Upfront laser interstitial thermal therapy (LITT) can be used as part of the treatment paradigm in difficult-to-access newly diagnosed glioblastoma multiforme (ndGBM) cases. The extent of ablation, though, is not routinely quantified; thus, its specific effect on patients' oncological outcomes is unclear. OBJECTIVE To methodically measure the extent of ablation in the cohort of patients with ndGBM and its effect, and other treatment-related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…We agree with Awan et al 1 regarding the potential of excess ablation contribution to glioblastoma patients' overall survival and progression-free survival, possibly similar to supramaximal resection accumulating data. In our study, no benefit regarding those oncological parameters was demonstrated.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We agree with Awan et al 1 regarding the potential of excess ablation contribution to glioblastoma patients' overall survival and progression-free survival, possibly similar to supramaximal resection accumulating data. In our study, no benefit regarding those oncological parameters was demonstrated.…”
supporting
confidence: 92%
“…We appreciate the letter to the editor submitted to the Neurosurgery journal recently by Awan et al 1 This letter addresses several important aspects of our work 2 that are to be clarified accordingly.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…13 Despite the growing literature supporting supramaximal resection in GBM, 14 ExA in this cohort did not show a positive effect on PFS or OS because of higher tumor residual in this group. 1 Therefore, we believe that optimization of the LITT-associated parameters to match ExA with supramaximal resection can potentially improve the LITT-related PFS and OS. The incorporation of preoperative mapping and intraoperative neuromonitoring in LITT planning may further contribute to achieve this goal.…”
mentioning
confidence: 96%
“…Kaisman-Elbaz et al 1 also report 84% of patients with excess ablation (ExA) (between 0.25 and 35.3 cc) performed with no neurological deficit. At least 75% of this cohort had lesions which were in deep or eloquent regions.…”
mentioning
confidence: 97%